Pertanggungjawaban Hukum Penggunaan Hak Potret oleh Penulis Alternative Universe Aplikasi X Ditinjau dari Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta - Tessa Trineni; Intan Maulida Nuripma (International Forum of Researchers and Lecturers, 2025)
The purpose of this article is to examine normatively how a person's liability for copyright infringement on portraits made in the framework of freedom of expression, namely writing stories, which means that it will methodologically question whether the existing liability by the author of Alternative Universe is in accordance with what is envisioned by the Copyright Law. The research methodology for the preparation of this article is through the type of normative research that views the law as a set of norms, one of which is a court decision. Through a statutory approach, the article is prepared with literature study data collection techniques and analyzes with a qualitative nature. This article concludes that the unauthorized use of portraits of public figures in commercial alternate universe (AU) fanfiction violates copyright, portrait rights, and moral rights, which can lead to both criminal and civil liability for the author, publisher, or production house. Although the publisher or producer is primarily responsible, the author can still be held liable for bad faith in using the work without permission. Therefore, creative industry players must understand and comply with legal provisions to avoid violations and the accompanying sanctions.